Field notes contributed by Peter C. Petersen, winter 1982-1983 - Petersen, Peter C.et al (1982)
Winter reports of birds and locations contributed by Peter C. Petersen. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1982-1983. Epson - sheet feed/flatbed